Automatic Generation of Coverage tests for System Programs (International Journal of Engineering and Computer Science, 2018)
Software testing is one of the critical activity for the organizations who spend lot of time and cost for the improvement of software quality. Programming testing is characterized as the way toward executing a project with the plan of discovering mistakes. Testing would ensure the correctness and produces reliable software. In order to achieve the quality software, sufficient number of test cases should be designed and tested.To calculate the integrity of test cases and identify that there are no unexpected functionalities, the structural code coverage should be measured like, statement or decision coverage.